Effectiveness of Stimulating Neural Branching Strategies in Developing Creative and Critical Thinking among Eighth Grade Students in Sultanate of Oman - Khadija A. Al Balushi; Sulaiman M. Al Balushi (Sultan Qaboos University, 2017)
This research aims to examine the effect of teaching by using strategies that stimulate neural branching in creative and critical thinking of study groups. The sample of this study consisted of two experimental groups and a control group. In terms of the treatment, one experimental group was taught using strategies that stimulate the neural branching in human brain mentally. The other experimental group was taught using the same strategies supported by technology. The control group was taught using the traditional instruction. The sample included (95) male student and (102) female students from two schools of the governorate of Muscat. To answer the research questions, Torrance test of creative thinking (TTCT) and Watson & Glaser critical thinking test (WGCTT) were used. The results show that the experimental groups significantly outperformed the control group with respect to the creative thinking test. However there were no statistically significant differences between the study's groups in the critical thinking test. This study recommends investment of mental capacities of the learners to encourage creative thinking and train teachers on using methods that stimulate neural branching.